PENGARUH PENAMBAHAN FLY ASH (ABU TERBANG) DAN ABU SEKAM PADI TERHADAP KUAT TEKAN BATA MERAH PEJAL KONVENSIONAL - Prakoso, Bimo; Elhusna, Elhusna; Wahyuni, Ade Sri (Inersia: Jurnal Teknik Sipil, 2018)
Red brick is a building element used in the construction of buildings and made of clay plus water with or without material mixture of other materials. Fly ash and rice husk ash contain silica. Silica is a material that has the nature of pozzolan which can increase the compressive strength of the brick when mixed with the soil. This study aims to determine the effect of the addition of fly ash and rice husk ash (ASP) to the value of compressive strength of clay brick. The process of making the test specimen follows the procedure in the brick factory.Variations of specimens made were normal bricks and bricks with the addition of fly ashand rice husk ash (ASP) used were 5%, 10%, 15%, 20%, 25% and 30% to the weight of clay.The number of test specimens of each percentage of fly ash and rice husk ash (ASP) as much as 12 specimens. The method of testing of red brick strength is referred to SNI 15-20942000. The result of the research shows that the compressive strength of the clay brick has decreased from normal clay brick by 38,97 kg/cm². The biggest decrease in compressive strength value obtaines at clay brick with 30% ashes (48,04%) and the smallest decreased obtaines at clay brick compressive strength in clay brick with 5% ash (5,98%). The decrease of the compressive strength is influenced by the amount of ash addition, water quantity and moisture content.